A Nanostructural Investigation of Glassy Gelatin Oligomers: Molecular Organization and Interactions with Low Molecular Weight Diluents - Enrione, J (IOP PUBLISHING LTD, 2012)
The effects of low molecular weight diluents (namely water and glycerol) on the nanostructure and thermodynamic state of low water content gelatin matrices are explored systematically by combining positron annihilation lifetime spectroscopy (PALS) with calorimetric measurements. Bovine gelatin matrices with a variation in the glycerol content (0-10 wt.%) are equilibrated in a range of water activities (a w = 0.11-0.68, T = 298 K). Both water and glycerol reduce the glass transition temperature, T g, and the temperature of dissociation of the ordered triple helical segments, T m, while having no significant effect on the level of re-naturation of the gelatin matrices. Our PALS measurements show that over the concentration range studied, glycerol acts as a packing enhancer and in the glassy state it causes a nonlinear decrease in the average hole size, ? h, of the gelatin matrices. Finally, we report complex changes in ? h for the gelatin matrices as a function of the increasing level of hydration. At low water contents (Q w ? 0.01-0.10), water acts as a plasticizer, causing a systematic increase in ? h. Conversely, for water contents higher than Q w ? 0.10, ? h is found to decrease, as small clusters of water begin to form between the polypeptide chains. © IOP Publishing Ltd and Deutsche Physikalische Gesellschaft.